Pelatihan Kegiatan Tahsin AlQuran Menggunakan Metode Ummi di Masjid Baitul Amal Kota Padang - Hidayat, Ajat; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2023)
The variety of methods in studying the Koran aims to ensure that Muslims can easily learn the Koran regardless of various obstacles. One of them is the Ummi Method, where this method is like a mother teaching her child. This training aims to encourage participants' interest in reading the Koran and their ability to read well and correctly according to the rules of reading the Koran using the Ummi Method. The method that the service uses is the Participatory Action Research (PAR) approach, where this research is oriented towards empowerment and change in society. It is clear that this service is oriented towards changing the quality of Al-Quran reading through the Ummi method. Then the implementation of the Ummi method uses two stages, namely direct and repetition where the teacher will model a reading, and then the participants will be asked to repeat the reading until they have completely perfected their reading. Then in this research there are two stages, namely 1) repeating memorization, and 2) correcting reading. writing activities Class action service. The subjects in this activity were 18 participants in the Baitul Amal Mosque Al-Quran tahsin. The results of this service explain that the Ummi method training in Al-Quran tahsin activities went well, marked by the increasing enthusiasm of the tahsin participants for reading the Al-Quran and there was some increase in the pronunciation of the makhorijul letters in reading the QS surah. al-`Alaq, QS. al-Zalzalah, and QS. al-`Adiyat.